Comparative Effectiveness of Lumbar Transforaminal Epidural Steroid Injections with Particulate Versus Nonparticulate Corticosteroids for Lumbar Radicular Pain due to Intervertebral Disc Herniation: A Prospective, Randomized, Double‐Blind Trial - Kennedy, David J.; Plastaras, Christopher; Casey, Ellen; Visco, Christopher J.; Rittenberg, Joshua D.; Conrad, Bryan; Sigler, James; Dreyfuss, Paul (Pain medicine (Malden, Mass.), 2014)
Background Lumbar transforaminal epidural injections are commonly utilized to treat radicular pain due to intervertebral disc herniation. Objective This study aims to determine if there was a major difference in effectiveness between particulate and nonparticulate corticosteroids for acute radicular pain due to lumbar disc herniation. Design A multicenter, double blind, prospective, randomized trial on 78 consecutive subjects with acute uni‐level disc herniation resulting in unilateral radicular pain. All subjects received a single level transforaminal epidural steroid injection with either dexamethasone or triamcinolone. Repeat injections were allowed as determined by the blinded physician and subjects. Primary outcomes included: number of injections received, surgical rates, and categorical pain scores at 2 weeks, 3 months, and 6 months. Secondary outcomes included mean Oswestry Disability Index. Results Both triamcinolone and dexamethasone resulted in statically significant improvements in pain and function at 2 weeks, 3 months, and 6 months, without clear differences between groups. The surgical rates were comparable with 14.6% of the dexamethasone group and 18.9% of the triamcinolone group receiving surgery. There was a statistically significant difference in the number of injections received, with 17.1% of the dexamethasone group receiving three injections vs only 2.7% of the triamcinolone group. Conclusions Transforaminal epidural corticosteroid injections are an effective treatment for acute radicular pain due to disc herniation, and frequently only require 1 or 2 injections for symptomatic relief. Dexamethasone appears to possess reasonably similar effectiveness when compared with triamcinolone. However, the dexamethasone group received slightly more injections than the triamcinolone group to achieve the same outcomes.